The relative influence of maternal nutritional status before and during pregnancy on birth outcomes in Vietnam. (November 2015) - Young, Melissa F.; Nguyen, Phuong Hong; Addo, O. Yaw; Hao, Wei; Nguyen, Hieu; Pham, Hoa; Martorell, Reynaldo; Ramakrishnan, Usha
Abstract: Objective: This study aimed to: (1) examine the role of multiple measures of prepregnancy nutritional status (weight, height, body composition) on birth outcomes (low birth weight (LBW), small for gestational age (SGA), preterm, birth weight, birth length, infant head circumference and mid-upper arm circumference (MUAC)); (2) assess relative influence of maternal nutritional status before and during (gestational weight gain) pregnancy on birth outcomes. Study design: We used prospective data on maternal body size and composition collected from women who participated in a randomized controlled trial evaluating the impact of preconceptional micronutrient supplements (PRECONCEPT) on birth outcomes in Thai Nguyen province, Vietnam ( n  = 1436). Anthropometric measurements were obtained before conception through delivery by trained health workers. The relationship between prepregnancy nutritional status indicators, gestational weight gain (GWG) and birth outcomes were examined using generalized linear models, adjusting for potential confounding factors. Results: Maternal prepregnancy weight (PPW) was the strongest anthropometric indicator predicting infant birth size. A 1 standard deviation (SD) increase in PPW (5.4 kg) was associated with a 283 g (95%CI: 279–286) increase in birthweight. A similar and independent association was observed with birthweight for an increase of 1 SD in gestational weight gain (4 kg) (250 g; 95% CI: 245–255). Women with a PPW <43 kg or who gained <8 kg during their pregnancy were more likely to give birth to a SGA (OR 2.9: 95%CI 1.9–4.5, OR 3.3: 95%CI 2.2–5.1) or LBW infant (OR 3.1: 95%CI 1.5–6.2, OR 3.4: 95%CI 1.6–7.2), respectively. Conclusions: These findings indicate that clinical care and programs aimed at improving birth outcomes will have the greatest impact if they address maternal nutrition both before and during pregnancy. Women with a PPW <43 kg or a GWG <8 kg are at greatest risk for poor birth outcomes in this setting. Preconception counseling and clinical care to obtain a healthy weight prior to pregnancy along with routine obstetric care on gestational weight gain is critical to improve birth outcomes. Trial registration: NCT01665378 (https://clinicaltrials.gov/show/NCT01665378 ).